Femoral Geometry in Male Patients with Atraumatic Hip Fracture - Original Investigation - Gülten Tan; Bengi Öz; Neşe Ölmez; Asuman Memiş; Berna Vidinli; Mehmet Özdemir (Türk Osteoporoz Dergisi, 2007)
Aims: Hip fracture is the most serious complication of osteoporosis and the most disabling type of fracture. In this study, we aimed to compare femoral geometry in hip fractured male patients aged more than 65 years old with age matched controls. Patients and Methods: 20 male patients with a history of nontraumatic hip fracture and 19 age-matched healthy controls were included in this study. Bone mineral density of neck and trochanter of hip were measured by DEXA. In addition to BMD, an experienced radiologist measured proximal femur geometric parameters potentially involved in bone strength. Results: Mean BMDs of trochanteric region were not significantly different between groups, but mean BMDs of neck region were statistically significantly lower in the hip fractured group. Neck shaft angle and femur shaft width were the geometric parameters found to be significantly higher in the hip fractured group. The correlation between femur geometric and the anthropometric measurements was present only in the kontrol group. Conclusion: We concluded that besides femur geometric measurements, correlation between these measurements might be an important factors for the fracture risk. (From the World of Osteoporosis 2007;13:15-8)